Pemanfaatan Lumpur Limbah Cair Industri Crumb Rubber Sebagai Adsorben Ion Cr(VI) yang Diaktivasi dengan KOH - Mardiati Mardiati; Salmariza Sy; Mawardi Mawardi (Jurnal Periodic Jurusan Kimia UNP, 2013)
Wastewater treatment with activated sludge method creates other waste in sludge form that becomes new problem for the crumb rubber industry. It is necessary to find a solution for their utilization. Research on utilization of sludge of  crumb rubber industry as an adsorbent of ion Cr (VI), which is activated by KOH has been carried out with variations treatment of adsorbent from fresh sludge and from the sludge that carbonized and activated with KOH. The results revealed that the sludge contain high silica and alumina which is 49.02% and 16.498% respectively, that mean it can be used as an adsorbent.  The optimum adsorbent pH of activated sludge was pH1 and pH2 for fresh sludge. The optimum contact time obtained at 120 minutes and the optimum concentration of Cr (VI) for each adsorbent was 70 mg / L. the maximum absorption capacity for Cr (VI) adsorption by Langmuir equation by activated sludge adsorbent is at 2.232 mg / g fresh sludge and adsorbent for 2,075  mg / g.